Plano de aproveitamento de jazida de areia, argila e turfa em planície de inundação do rio Mogi Guaçu, SP - STEIN, Dirceu Pagotto (2019)
This work deals with technical procedures required by DNPM (Departamento Nacional de Produção Mineral) in order to get the mining rights related to mineral explotation, in accordance with the brazilian mineral law. The mineral deposit , in this case, is composed by sand, clay and peat ores hosted in the Mogi-Guaçu river’s alluvial plain, located in the northeast region of the São Paulo State. The explotation plan aims to maximize the mining of these ores and economic profits. The goal in this case, is to develop the extraction of these ores in a sequential way. At first with peat and clay being exploted in dry open pit and then to extract sand in flooded open pit, under geotechnical stability conditions. Environmental care will be kept as well environmental recovery, according to the future use project of the area. The study ends with the economic analysis by using the discounted cash flow method, taking in account the present value and rate of return consistent with the financial effort. The results indicate a satisfactory mining project in terms of investment and risk, with attractive return values.